HTML, the definitive guide - Musciano, Chuck (O'Reilly, 1997)
HTML: The Definitive Guide helps you both ways: the authors cover every element of HTML in detail, explaining how each element works and how it interacts with other elements. Many hints about HTML style help you accomplish a variety of tasks, from simple online documentation to complex marketing and sales presentations. With hundreds of examples, the book gives you models for writing your own effective Web pages and mastering advanced features, like style sheets and frames.